2017
DOI: 10.14573/altex.161102
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of a metabolizing system in biodetection assays for endocrine active substances

Abstract: Among the in vitro assays for the detection of endocrine active substances (EAS), the CALUX assay (Chemically Activated LUciferase gene eXpression) allows the detection of substances (i.e., ligands) with the potential to interact with various nuclear receptors and affect the subsequent transcriptional response (Sonneveld et al., 2005). Such assessments generally fail to take into account the role of metabolism. Indeed, the majority of cell-based assays use cells that are not metabolically competent and do not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…All referred in vitro-based assays detecting strong oxidative stress response used (hepatic) cell lines that are capable of active metabolization. Hence, future experiments focusing on petroleum-induced toxicity in the U2-OS cell line should consider the simulation of a vertebrate xenobiotic biotransformation system (e.g., S9 fraction obtained from rat livers) [41,59].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…All referred in vitro-based assays detecting strong oxidative stress response used (hepatic) cell lines that are capable of active metabolization. Hence, future experiments focusing on petroleum-induced toxicity in the U2-OS cell line should consider the simulation of a vertebrate xenobiotic biotransformation system (e.g., S9 fraction obtained from rat livers) [41,59].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…This estrogenic activity was significantly increased when the activated S9 fraction was added to the assay (EC 50 0.15 μM), which suggested the formation of active metabolites of methoxychlor. The pure methoxychlor metabolite 4,4 0 -(2,2,2trichloroethane-1,1-diyl) diphenol was also tested, and its estrogenic activity was comparable with that of methoxychlor treated with the S9 fraction (EC 50 0.05 μM), which suggested that 4,4 0 -(2,2,2-trichloroethane-1,1-diyl) diphenol is the main metabolite formed with the S9 fraction [32]. As the methoxychlor metabolites mono-OH methoxychlor and bis-OH-methoxychlor are formed both in vitro and in vivo, addition of the metabolic enzymes here (i.e., the S9 fraction) improved the in vivo prediction [33].…”
Section: Metabolic Activation Of Proestrogensmentioning
confidence: 96%
“…While methoxychlor has no estrogenic activity, its mono-demethylated and bis-demethylated metabolites have significant estrogenic activities [31]. Mollergues et al determined the estrogenic activity of methoxychlor using the ER-CALUX assay with and without the β-naphthoflavone-/phenobarbital-induced S9 fraction [32]. In this assay, methoxychlor showed weak estrogenic activity (EC 50 4.6 μM).…”
Section: Metabolic Activation Of Proestrogensmentioning
confidence: 99%
“…In the current study we show that the CALUX system has very low basal metabolic competence. Therefore we have developed a metabolic module using rat liver S9 as an add-on to the CALUX assays; a proof-of-principle of this method was published recently [19]. In genotoxicity testing, mimicking in vivo hepatic metabolism using S9 fractions is common practice [20][21][22].…”
Section: Introductionmentioning
confidence: 99%